2012
DOI: 10.1111/j.1600-0625.2012.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

KU812 basophils express urocortin, CRHR, MC1R and steroidogenic enzymes and secrete progesterone

Abstract: Little is known about neuroendocrine regulation of human basophils by components of the hypothalamic-pituitaryadrenal (HPA) axis. Using the basophil cell line KU812 as an in vitro model, we show that these cells express urocortin 1-3, specific isoforms of the corticotropin-releasing hormone (CRH) receptor (CRH-R)1 and CRH-R2 but not CRH itself. The precursor for melanocortins and b-endorphin, proopiomelanocortin, was not detectable, while the melanocortin-1 receptor was present at RNA and protein level in KU81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This was based on two key observations: (i) that TSPO contained a cholesterol‐binding domain; and (ii) that TSPO density was high in steroid synthesizing cells such as Leydig cells 45,46 . The hypothesis that immune cell surface expression of TSPO is involved in steroidogenesis in these cells would be highly unlikely as immune cells produce little to no steroid proteins 47 . The potential role of TSPO in cholesterol transport, however, could have biologic implications for immune cells with TSPO on their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was based on two key observations: (i) that TSPO contained a cholesterol‐binding domain; and (ii) that TSPO density was high in steroid synthesizing cells such as Leydig cells 45,46 . The hypothesis that immune cell surface expression of TSPO is involved in steroidogenesis in these cells would be highly unlikely as immune cells produce little to no steroid proteins 47 . The potential role of TSPO in cholesterol transport, however, could have biologic implications for immune cells with TSPO on their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 The hypothesis that immune cell surface expression of TSPO is involved in steroidogenesis in these cells would be highly unlikely as immune cells produce little to no steroid proteins. 47 The potential role of TSPO in cholesterol transport, however, could have biologic implications for immune cells with TSPO on their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The human gut and colon cancer cells also express glucocorticosteroidogenic activity with production of cortisol and corticosterone and expression of CYP11A1, CYP17A1 and CYP11B1 [4951]. Other organs which display local steroidogenic pathways in humans are the heart, skin and cells of the immune system (see Table 2) including human basophils [52]. Table 3 shows the expression of steroidogenic genes in different cancers, illustrating their likely capacity to synthesize and/or metabolize steroid hormones as has already been shown with melanoma cells [53, 54].…”
Section: Steroidogenesis In the Skinmentioning
confidence: 99%
“…We recently showed that CD300a is upregulated in basophils in mixed leucocyte cultures , and our current aims were to assess its effects on mediator release and signalling using purified basophils. As basophils contribute to the pathophysiology of several skin diseases, particularly allergies , as well as potentially regulating key immunological and even neuroendocrine functions , there is a pressing need to investigate inhibitory mechanisms that can used as therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%